Health care expenditure and income in the OECD reconsidered: Evidence from panel data - Badi H. Baltagi; Francesco Moscone (Institute for the Study of Labor (IZA), 2010)
This paper reconsiders the long-run economic relationship between health care expenditure and income using a panel of 20 OECD countries observed over the period 1971-2004. In particular, the paper studies the non-stationarity and cointegration properties between health care spending and income. This is done in a panel data context controlling for both cross-section dependence and unobserved heterogeneity. Cross-section dependence is modelled through a common factor model and through spatial dependence. Heterogeneity is handled through fixed effects in a panel homogeneous model and through a panel heterogeneous model. Our findings suggest that health care is a necessity rather than a luxury, with an elasticity much smaller than that estimated in previous studies.
Keywords: C31; C33; H51; 330; Health expenditure; income elasticity; cross section dependence; heterogeneous panels; factor models; Gesundheitsvorsorge; Gesundheitskosten; Einkommen; Panel; OECD-Staaten